Mary R. Musgrove letter to Thomas H. Kent regarding field notes of a Snowy Owl sighting, February 9, 1982 - Musgrove, Mary R.et al (1982)
Field notes were contributed by Mary R. Musgrove in a letter to Thomas H. Kent. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1981-1982. Epson - sheet feed